2017
DOI: 10.1161/circinterventions.116.004909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Forward Stroke Volume Response on Clinical and Structural Outcomes After Percutaneous Mitral Valve Repair With MitraClip

Abstract: Background-An increase of systolic forward flow was frequently observed after successful MitraClip implantation in patients with significant mitral regurgitation. However, the impact of systolic forward flow improvement on postMitraClip outcomes remains unknown. Methods and Results-Study population included 160 patients who underwent successful MitraClip implantation. The systolic forward flow was noninvasively calculated as the forward stroke volume (FSV) at baseline before the MitraClip procedure and before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…18,19 Based on the COAPT trial, 20 MitraClip therapy is considered a favorable option for the treatment of heart failure, and is also expected to be a good option for renal congestion. The forward stroke volume is increased after TEER, 21 which should improve hemodynamics and result in improved renal congestion. Among the present patients who had a discontinuous IRVF pattern prior to MitraClip therapy, the majority demonstrated improvement in MR grade; however, only 30% showed an improvement to a continuous IRVF pattern following MitraClip therapy (Supplementary Figure).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Based on the COAPT trial, 20 MitraClip therapy is considered a favorable option for the treatment of heart failure, and is also expected to be a good option for renal congestion. The forward stroke volume is increased after TEER, 21 which should improve hemodynamics and result in improved renal congestion. Among the present patients who had a discontinuous IRVF pattern prior to MitraClip therapy, the majority demonstrated improvement in MR grade; however, only 30% showed an improvement to a continuous IRVF pattern following MitraClip therapy (Supplementary Figure).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this hypothesis, LVOT-VTI showed the highest C-statistics for the prediction of cardiac death, while the calculation of an optimal prognostic cut-off (17 cm) allowed an accurate stratification of patient risk over the follow-up (Log rank 44.3, p < 0.001). Interestingly, in a sub-analysis of the EVEREST II trial [26], percutaneous edge-to-edge mitral valve repair was associated with a greater hemodynamic and clinical improvement in the patients with a lower baseline forward LV flow. Considering the retrospective nature of the present work, further well-designed prospective studies should clarify whether the integration of LVOT-VTI with other clinical and instrumental parameters, such as EROA and GLS, may optimize the selection of the patients with HF and functional MR which could benefit more from mitral valve intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that an increase in stroke volume after MitraClip implantation (stroke volume at discharge divided by stroke volume at baseline, discharge/baseline ratio) was associated with a more favourable outcome. Further, patients with an increase in stroke volume after the MitraClip implantation had a significantly more severe MR at baseline and a significantly lower stroke volume at baseline [ 22 ].…”
Section: Discussionmentioning
confidence: 99%